2017
DOI: 10.1021/acs.jmedchem.7b00426
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS3/4A Protease Inhibitors Incorporating Flexible P2 Quinoxalines Target Drug Resistant Viral Variants

Abstract: A substrate envelope-guided design strategy is reported for improving the resistance profile of HCV NS3/4A protease inhibitors. Analogues of 5172-mcP1P3 were designed by incorporating diverse quinoxalines at the P2 position that predominantly interact with the invariant catalytic triad of the protease. Exploration of structure-activity relationships showed that inhibitors with small hydrophobic substituents at the 3-position of P2 quinoxaline maintain better potency against drug resistant variants, likely due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 51 publications
5
58
0
Order By: Relevance
“…S1), and we have previously shown that inhibitors must fit within the envelope to have a flat profile against resistance (37)(38)(39). Relocating the macrocyle to fit within the substrate envelope in 5172-mcP1P3 (35) and the closely related parent compound (35) (Fig. 1) indeed achieved a flatter resistance profile than that of grazoprevir but unfortunately resulted in potency loss against the WT protease in enzymatic assays.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…S1), and we have previously shown that inhibitors must fit within the envelope to have a flat profile against resistance (37)(38)(39). Relocating the macrocyle to fit within the substrate envelope in 5172-mcP1P3 (35) and the closely related parent compound (35) (Fig. 1) indeed achieved a flatter resistance profile than that of grazoprevir but unfortunately resulted in potency loss against the WT protease in enzymatic assays.…”
Section: Resultsmentioning
confidence: 75%
“…The resulting inhibitor, 5172-mcP1P3, was less susceptible to single-site RASs, particularly A156T (29), and the crystal structures validated that the binding mode of the P2 quinoxaline moiety stacking against catalytic residues was retained (31). Further optimization by modifications at the 3-position of the P2 quinoxaline moiety to decrease interactions with the S2 subsite residues Arg155 and Ala 156 revealed that compounds with a smaller methyl group at this position retains better activity against resistant variants (35). The resulting inhibitor ( Fig.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…[2] Most of these well-developed methods are focused on copper-, [2,3] palladium-, [2,4] and nickel-catalyzed fluoroalkylations, [2,5] while the use of inexpensive,n ontoxic and environmentally benign transition metals,s uch as iron, as ac atalyst remains appealing.F or instance,although the iron-catalyzed Kumada reactions have been well established since Kochisp ioneering work, [6,7] the iron-catalyzed fluoroalkylations between Grignard reagents and fluoroalkyl halides has not been reported thus far because traditional catalytic systems often lead to defluorination reactions. [9] Inspired by the previous work on iron/TMEDA( L1) catalyzed cross-couplings between Grignard reagents and alkyl halides, [10] we initially focused our efforts on the crosscoupling of phenyl magnesium bromide (1a)w ith the unactivated difluoroalkyl bromide 2a in the presence of FeCl 3 (10 mol %) with TMEDA( L1;1 0mol %) as al igand (Scheme 1a). [9] Inspired by the previous work on iron/TMEDA( L1) catalyzed cross-couplings between Grignard reagents and alkyl halides, [10] we initially focused our efforts on the crosscoupling of phenyl magnesium bromide (1a)w ith the unactivated difluoroalkyl bromide 2a in the presence of FeCl 3 (10 mol %) with TMEDA( L1;1 0mol %) as al igand (Scheme 1a).…”
mentioning
confidence: 99%
“…[8] Herein, we report the first example of ironcatalyzed difluoroalkylation of arylmagnesiums with difluoroalkyl bromides.T he approach allows av ariety of difluoroalkyl bromides,i ncluding gaseous bromodifluoromethane, and provides ag eneral and cost-efficient method to difluoroalkylated arenes,adistinct class of fluorinated compounds found in many biologically active molecules. [9] Inspired by the previous work on iron/TMEDA( L1) catalyzed cross-couplings between Grignard reagents and alkyl halides, [10] we initially focused our efforts on the crosscoupling of phenyl magnesium bromide (1a)w ith the unactivated difluoroalkyl bromide 2a in the presence of FeCl 3 (10 mol %) with TMEDA( L1;1 0mol %) as al igand (Scheme 1a). However, the desired difluoroalkylated arene 3a was not obtained because of the severe defluorination of 2a.T he slow addition of 1a to the reaction system showed abeneficial effect, but only 20 %yield of 3awas obtained and the defluorination reactions remained al arge hurdle.T o address this crucial issue,asuitable catalytic iron system is essential.…”
mentioning
confidence: 99%